Uji Kesiapan Minyak Cengkeh Sebagai Lotion Massage Pada Ibu Nifas - Hi Saraha, Rosida; S. Hasan, Mayang Sari; Ali, Hikmawati (Jurnal Kebidanan Malakbi, 2025)
Postpartum fatigue can be addressed through pharmacological and non-pharmacological/traditional approaches. One common non-pharmacological intervention is light physical exercise such as swimming, aerobics, yoga, cycling, and massage. Massage is a form of traditional medicine that has been passed down through generations and is believed to have health benefits, including improving sleep quality and body relaxation. Massage with the right technique is believed to improve overall health. In its implementation, massage often uses lotions, oils, or balms as lubricants to facilitate movement. Clove oil, extracted from the Syzygium aromaticum plant native to Maluku, Indonesia, has analgesic properties that have been shown to relieve postpartum musculoskeletal pain. Furthermore, the aroma produced by clove oil has the potential to provide a relaxing effect and reduce stress levels in mothers. This research aims to develop a clove oil-based lotion formulation that will be used in massage practice. The research design used is a clinical trial consisting of several stages. These stages include obtaining ethical approval, permits from Kesbangpol (Ministry of Home Affairs), laboratory permits, and finally the lotion formulation process. The evaluation of the clove oil lotion preparation formula D for postpartum massage involved testing viscosity, pH, organoleptic properties, homogeneity, spreadability, and adhesion. The results showed that the lotion was white in color with a distinctive clove aroma, had a viscosity of 5620 cps which was in accordance with standards, a pH of 5.96 which met SNI standards, a good spreadability value of 6.9 cm, and a very good adhesion value of 4.37 seconds. The sensitivity test also showed negative results, which means the lotion did not cause irritation. Based on these test results, it can be concluded that the clove oil lotion preparation formula D was successfully formulated after four trials.